2020
DOI: 10.3390/nu12051298
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intakes during Weaning from Parenteral Nutrition Drive Growth Gain and Body Composition in Very Low Birth Weight Preterm Infants

Abstract: Weaning from parenteral to enteral nutrition is a critical period to maintain an adequate growth in very low birth weight preterm infants (VLBWI). We evaluated the actual daily nutritional intakes during the transition phase (TP) in VLBWI with adequate and inadequate weight growth velocity (GV ≥ 15 vs. GV < 15 g/kg/day). Fat-free mass (FFM) at term-corrected age (TCA) was compared between groups. Based on actual nutritional intakes of infants with adequate growth, we defined a standardized parenteral nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Nutrition management during this transitional period must be carefully evaluated and modified to meet infant needs, especially given the length of this period may vary significantly based on unit nutrition protocols, birth weight and/or gestational age, and infant illness severity. Liotto et al demonstrated the importance of close observation and monitoring during the transitional phase, as low protein provision during this period was associated with decreased growth velocity and fat-free mass composition at term-corrected age in very low birth weight infants [ 84 ]. Likewise, Brennan et al compared hourly intakes of macronutrients during the transitional phase, exemplifying the need for higher parenteral volume when enteral feeding was <40 mL/kg/day as well as early fortification of human milk to achieve targeted protein provision when infants began receiving more enteral compared to parenteral nutrition [ 85 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Nutrition management during this transitional period must be carefully evaluated and modified to meet infant needs, especially given the length of this period may vary significantly based on unit nutrition protocols, birth weight and/or gestational age, and infant illness severity. Liotto et al demonstrated the importance of close observation and monitoring during the transitional phase, as low protein provision during this period was associated with decreased growth velocity and fat-free mass composition at term-corrected age in very low birth weight infants [ 84 ]. Likewise, Brennan et al compared hourly intakes of macronutrients during the transitional phase, exemplifying the need for higher parenteral volume when enteral feeding was <40 mL/kg/day as well as early fortification of human milk to achieve targeted protein provision when infants began receiving more enteral compared to parenteral nutrition [ 85 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…35 During the transition from PN to EN, infants in both groups received adequate and comparable protein, energy, and protein-energy ratios. 36 The significantly higher weekly nutrient provision in the short-PN group is expected, considering the higher proportion of their nutrition being provided enterally and the higher enteral macronutrient requirements to compensate for intestinal digestion and hepatic first-pass metabolism. The difference in BM exposure might be another factor at play; infants in the short-PN group had significantly more BM exposure.…”
Section: Discussionmentioning
confidence: 97%
“…4,17,39 It is possible that the comparable EN initiation and advancement and PN durations in previous studies masked their effect on FFM accretion. 4,8,36,40,41 Furthermore, the correlation between delayed enteral feeding and dysbiosis could theoretically stimulate low-grade chronic inflammation and could be implicated in the pathogenesis of insulin resistance and metabolic syndrome. 42,43 Further studies are ongoing by this group to describe the relationship between neonatal body composition and gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a very vulnerable period, since the absorption of various nutrients from the intestinal lumen to the splanchnic district varies according to the type of amino acids. Therefore, it is crucial to carefully perform this transition to ensure adequate intake, mainly of protein, and consequently achieve adequate growth [20][21][22].…”
mentioning
confidence: 99%